Temperature characteristics of silicon nanowire transistor depending on oxide thickness - AlAriqi, Hani Taha; Jabbar, Waheb A.; Hashim, Yasir; Hadi, Manap (Sumy State University, 2019)
Among various sensing and monitoring techniques, sensors based on field effect transistors (FETs) have attracted considerable attention from both industry and academia. Owing to their unique characteristics such as small size, light weight, low cost, flexibility, fast response, stability, and ability for further downscaling, silicon nanowire field effect transistor (SiNW-FET) can serve as an ideal nanosensor. It is the most likely successor to FET-based nanoscale devices. However, as the dimensions (channel length and diameter) of SiNWT channel are shrinking down, electrical and temperature characteristics of SiNWTs should be affected, thereby degrading transistor performance. Although applications of SiNWTs as biological and/or chemical sensors have been extensively explored in the literature, less attention has been devoted to utilize such transistors as temperature sensors. Therefore, this paper characterizes the temperature sensitivity of SiNWT depending on the channel oxide thickness and also presents the possibility of using it as a nano-temperature sensor. The MuGFET simulation tool was used to investigate temperature characteristics of the nanowire. Current-voltage characteristics with different values of temperature and with different thickness of the nanowire gate (oxide thickness (TOX) = 1, 2, 3, 4, and 5 nm), were simulated. Metaloxide- semiconductor (MOS) diode mode connection was suggested for measuring the temperature sensitivity of SiNWT. Several operating voltages (0.25 to 5 V) with various working temperature (250 to 450 K) were investigated. The obtained results show that the highest temperature sensitivity was achieved by increasing oxide thickness to 5 nm. The impact of the considered temperature on SiNWT characteristics demonstrates the possibility of utilizing it as a temperature nanosensor.